Autonomic dysreflexia during pregnancy in a woman with spinal cord injury: a case report. Issue 7 (July 2019) - Soh, Soo-Hyun; Lee, Geonsang; Joo, Min Cheol
We herein report a case involving a 35-year-old woman with spinal cord injury (SCI) in whom autonomic dysreflexia (AD) newly developed during pregnancy and resolved after delivery. The neurological level and severity of SCI according to the American Spinal Injury Association Impairment Scale (AIS) was T4 AIS-A. The patient had sustained an SCI 20 years prior. Upon presentation, she reported a newly developed increased need to empty her bladder, facial flushing, palpitation, sweating, and headache during pregnancy. She was hospitalized for careful observation at 33 weeks of gestation. The intensity and frequency of the symptoms of AD increased with time. She underwent a cesarean section under general anesthesia at 36 weeks of gestation. Three weeks after the delivery, her vital signs normalized and AD symptoms improved. This case indicates that careful evaluation and proper management of AD symptoms in pregnant women with SCI are essential. For proper prevention and management of AD, education about AD symptoms and supportive management to prevent AD symptoms are necessary for the patient, physician, and multidisciplinary approach team.